2017
DOI: 10.18632/oncotarget.18845
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of methylenetetrahydrofolate reductase tagging polymorphisms with colorectal cancer in Chinese Han population

Abstract: The aim of this case-control study was to assess the relationship between the tagging polymorphisms in methylenetetrahydrofolate reductase (MTHFR) gene and the susceptibility to colorectal cancer (CRC) in a Chinese Han population. A custom-by-design 48-Plex SNPscan Kit was used to determine the genotypes of MTHFR rs3753584 T>C, rs9651118 T>C, rs1801133 G>A, rs4846048 A>G and rs4845882 G>A polymorphisms in 387 CRC patients and 1,536 non-cancer controls. The results revealed that MTHFR rs1801133 G>A polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This cohort was in part previously studied (19, 26). The CRC cases were recruited from Fujian Medical University Union Hospital (Fuzhou city, China) and the Affiliated People's Hospital of Jiangsu University (Zhenjiang city, China) between October 2014 and August 2017.…”
Section: Methodsmentioning
confidence: 99%
“…This cohort was in part previously studied (19, 26). The CRC cases were recruited from Fujian Medical University Union Hospital (Fuzhou city, China) and the Affiliated People's Hospital of Jiangsu University (Zhenjiang city, China) between October 2014 and August 2017.…”
Section: Methodsmentioning
confidence: 99%
“…[9–12] A large number of epidemiological studies have investigated the relationship between the C677T polymorphism of MTHFR and many diseases, including breast cancer, colorectal cancer, ischemic stroke, depressive disorders, and hypertension. [1317]…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [43] suggested that MTHFR rs3753584 locus affected the development of lung cancer. Another study found that MTHFR rs3753584 variants increased the susceptibility of colon cancer [44]. Here, we identified that MTHFR rs3753584 may confer a risk to HCC.…”
Section: Discussionmentioning
confidence: 52%